Implementasi Metode MD2 Untuk Otentikasi Hasil Scan Citra Ijazah - Winda Wulan Sari (STMIK Budi Darma, 2021)
A diploma is one of the requirements for someone who wants to apply for a job, but sometimes to getthis, someone can commit fraud by falsifying the contents of the certificate. Forthat we need a system that can provide authentication of a diploma image. This research uses a cryptographic algorithm that will becombined with image processing to ensure the security of an image or certificate. In this study, there is an insertion process and a security process that uses the MD2 method as a medium for solving the implementation of the Authentication of the Ijazah image scan. The results of this study indicate that the authentication application can detect diploma manipulation.